(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
The potential and prospect of fish farming of Sreemangal, Moulvibazar was carried out from January to December 2015 by interviewing of 90 fish farmers with a well-structured questionnaire. The survey revealed that 40% of the ponds were seasonal and 60% perennial, of which 85% with single ownership and 15% accompanied by multiple ownership. The average pond size was 0.13 ha and depth 2.6 m. The ponds were prepared using of lime, cow dung, urea and TSP at the rate of 250, 250, 40 and 20 kg/ha, respectively. Nearly all of the farmers practiced polyculture with Indian major carps and exotic carps. Fish was stocked from March to June and average stocking density was 15,500 fingerlings/ha. To sustain natural food production, farmers generally used cow dung, urea and TSP at the rate of 2,600, 300 and 150 kg/ha/yr, respectively. Healthy environmental condition was maintained by applying lime and salt at 600 and 60 kg/ha/yr, respectively. The fish were fed by supplementary feed (45% farm) e.g., rice bran and mustard oil-cake with an average quantity of 2,200 and 550 kg/ha/yr, respectively and artificial pellet feed (55% farm). The average fish production, production cost and profit were found 2,945 kg/ha/yr, 1,25,940 and 94,935 Tk./ha/yr, respectively. The major constraints for sustainable pond fish farming were non-availability of fish fingerlings during stocking period, insufficient water in dry season, high production cost, poor technical knowledge, lack of money etc. By establishing more hatcheries, arranging training at farm level, providing interest free or at lower interest loan to the farmers the existing fish production could be increased. Res. Agric., Livest. Fish.3(2): 361-368, August 2016